Comparing the use of CSs by high and low proficient Spanish learners´ of English: Storytelling and Interview Tasks - Benali Taouis, Hanane (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This research suggests a comparison between two tasks to evaluate oral communication strategies (CSs) through storytelling and interview and to compare the use of CSs between high and low proficient students. The results of the storytelling and oral interview are compared to check if CSs vary with the task and what tasks are better for each of the selected CSs. A number of 60 Spanish learners of English participated in this investigation, and a total of 232 protocols were analysed to obtain the results. The main results are that CSs vary to adapt to task demands and that the frequency and type of CSs used by the students are affected by the level of proficiency of the students. This highlights the importance of selecting the appropriate task for the evaluation to be significant and the necessity to adapt the syllabus to include elements that introduce some productive CSs.